The integration process of the Lower Moesian areas - Duch, Michał (Studia Europaea Gnesnensia, 2017)
The objective of this article is to provide a short presentation of the integration process of the areas that formed Lower Moesia. The author aims to present select methods implemented by the Romans in order to place the discussed territories under their complete control. The main differences between the individual parts of Lower Moesia have also been indicated in the article, as well as the ways in which they mutually supplemented each other, ultimately composing a cohesive whole.